Upaya Pemenuhan Zat Besi Pada Ibu Hamil Trimester III Dengan Anemia - Rosita, Erni, Winarsih Nur Ambarwati, S.Kep, Ns, ETN, M.Kep (2017)
Background issues: Mother mortality showed the lower socioeconomic circumstances. One of the causes of it was anemia, and iron deficiency anemia is the common case that found. The highest incidence of it case was experienced by third-trimester pregnant women, approximately 66.9%, while 56.1% on second-trimester and only 47% on first-trimester. It could cause premature birth, lower birth weight, miscarriage and disability. While it could cause heart failure, fatigue and premature labour for the mothers. Purpose: could handle the pregnants at third-trimester by improving nutritions on them which based on nursing care standards. Methods: it used case study approach descriptive method on Miss. R by making the nursing care From the assessment, intervention, implementation and evaluation. Results: Efforts that were made to review the fulfillment of the iron on 3rd trimester pregnant women is encourages patients to review the consumption of foods containing Fe and vitamin C, encourages patients to consume the enhancer blood supplement, teaches them for combine spinach and tomato into juice, making sweet potato's leaf herbal, and providing information about the nutritional needs of pregnant women with anemia. The case of 3rd trimester of pregnancy with anemia is resolved, the intervention was stopped. Conclusion: 3rd trimester maternal anemia was resolved, it could be more effective to suggest them to consume enhancer blood supplement to improve the level of hemoglobin.